Learning Cultural Literacy through Creative Practices in Schools: Cultural and Multimodal Approaches to Meaning-Making - Lähdesmäki, Tuuli; Baranova, Jūratė; Ylönen, Susanne C; Koistinen, Aino-Kaisa; Mäkinen, Katja; Juškiene, Vaiva; Zaleskiene, Irena (Springer Nature, 2022)
This open access book discusses how cultural literacy can be taught and learned through creative practices. It approaches cultural literacy as a dialogic social process based on learning and gaining knowledge through emphatic, tolerant, and inclusive interaction. The book focuses on meaning-making in children and young people’s visual and multimodal artefacts created by students aged 5–15 as an outcome of the Cultural Literacy Learning Programme implemented in schools in Cyprus, Germany, Israel, Lithuania, Spain, Portugal, and the UK. The lessons in the program address different social and cultural themes, ranging from one’s cultural attachments to being part of a community and engaging more broadly in society. The artefacts are explored through data-driven content analysis and self-reflexive and collaborative interpretation and discussed through multimodality and a sociocultural approach to children’s visual expression. This interdisciplinary volume draws on cultural studies, communication studies, art education, and educational sciences.